Avoiding Full Lymphadenectomies in Intermediate- and High-Risk Endometrial Cancer by Sentinel Lymph Node Biopsy Implementation - Pineda, Virginia García; Zapardiel, Ignacio; Gracia, Myriam; Siegrist, Jaime; Diestro, María Dolores; Alonso, María; Hernández, Alicia (Frontiers in Oncology, 2021)
Objective To evaluate the role of sentinel lymph node biopsy (SLNB) to avoid staging lymphadenectomies by detecting nodal metastasis in intermediate- and high-risk endometrial cancer (EC). Methods A single institutional retrospective study was performed including all patients with intermediate- and high-risk EC who underwent surgical nodal staging between January 2012 and December 2019. Patients with disseminated disease detected on imaging techniques or at the time of surgery were excluded. Patients were evaluable if they underwent nodal staging with SLNB and pelvic (PLD) and paraaortic (PALD) lymph node dissection. We analyzed the accuracy of the sentinel lymph node technique. Only patients with at least one sentinel lymph node (SLN) detected were included in the sensitivity and negative predictive value (NPV) analyses. The tracers used were technetium 99m, blue dye, and indocyanine green. Results Eighty-eight patients presented intermediate- and high-risk EC (51 patients and 37 patients respectively) and underwent SLNB with consecutive PLD and PALD. The median (range) number of sentinel nodes retrieved was 2.9 (0–11). The global detection rate of SLN was 96.6% with a bilateral detection of 80.7% when considering all tracers used. However, when combination of indocyanine green and technetium was used the bilateral detection rate was 90.3%. Nodal metastases were detected in 17 (19.3%) cases, 8 (47%) of them corresponded to low volume metastasis (LVM), 7 (87.5%) of them diagnosed at ultrastaging pathologic exam. Finally, we obtained a sensitivity of 90%, a NPV of 97.5%, and a false negative rate (FNR) of 10% in the intermediate-risk EC compared to sensitivity of 85.7%, NPV of 96.6%, and FNR of 14.3% in the high-risk EC group. The only patient with isolated paraaortic nodal metastasis was found at the high-risk group, 1.1%. Conclusions According to our results, full lymphadenectomy could be avoided by performing SLNB in patients with intermediate-risk EC because the only false negative case detected was at the beginning of ICG learning curve. For high-risk EC patients we did not find enough evidence to support the systematic avoidance of staging full lymph node dissection. Nevertheless, SLNB should be performed in all cases of EC as it improves LVM diagnosis substantially.